Crisis style : the aesthetics of repair - Dango, Michael (Post 45., 2022)
"In this expansive and provocative new work, Michael Dango theorizes how aesthetic style manages crisis--and why taking crisis seriously means taking aesthetics seriously. Detoxing, filtering, binging, and ghosting: these are four actions that have come to define how people deal with the stress of living in a world that seems in permanent crisis. As Dango argues, they can also be used to describe contemporary art and literature. Employing what he calls "promiscuous archives," Dango traverses media and re-shuffles literary and art historical genealogies to make his case. The book discusses social media filters alongside the minimalism of Donald Judd and La Monte Young and the television shows West Wing and True Detective. It reflects on the modernist cuisine of Ferran Adrià and the fashion design of Issey Miyake. And, it dissects writing by Jenifer Egan, David Foster Wallace, David Mitchell, and Zadie Smith. Unpacking how the styles of these works detox, filter, binge, or ghost their worlds, Crisis Style is at once a taxonomy of contemporary cultural production and a theorization of action in a world always in need of repair. Ultimately, Dango presents a compelling argument for why we need aesthetic theory to understand what we're doing in our world today"--